Clinical epidemiological characteristics of patients diagnosed with SARS-CoV-2. Hospital I Florencia de Mora EsSalud – La Libertad, 2020: Características clinico epidemiológicas de pacientes con diagnóstico de SARS-CoV-2. Hospital I Florencia de Mora EsSalud – La Libertad, 2020 - Tejada-López, Yeny (2021)
Introduction: the SARS-CoV-2 pandemic affected a large part of the population of La Libertad, among them, the population of Florencia de Mora whose hospital played an important role in the care of patients diagnosed with COVID-19. Objective: to determine the epidemiological clinical characteristics of patients diagnosed with SARS-CoV-2 treated at the care center. Methods: Retrospective observational descriptive study, with a population of 2622 patients treated in the COVID-19 triage, taking into account the molecular test and the rapid serology test for the detection of SARS-CoV-2. Results: SARS-CoV-2 was detected in 74.90% (1155) of patients. The months with the highest number of cases were June and July with 29.4% (340) and 37.4% (432), respectively. The predominant age group was 27- 59 years with 77.9% (900) and males with 57.5% (664). Regarding the clinical profile, the most frequent comorbidity was hypertension with 6.9% (80), obesity and overweight with 3.7% (43) and the most frequent symptoms were cough 62.9% (726) and odynophagia 55.7% (643). Conclusions: 75 out of 100 screened patients had SARS-CoV-2, predominantly males, the age group of 27-59 years, hypertension, obesity and overweight as comorbidity, cough and odynophagia as the most frequent symptoms.